To solve the equation 4(2-3x) = x - 2(2x + 1), we can first simplify each side of the equation:
On the left side:
4(2-3x) = 8 - 12x
On the right side:
x - 2(2x + 1) = x - (4x + 2) = x - 4x - 2 = -3x - 2
Now our equation becomes:
8 - 12x = -3x - 2
To solve for x, let's combine like terms:
-12x + 3x = -2 - 8
-9x = -10
Dividing both sides of the equation by -9:
x = -10 / -9
x = 10/9
Therefore, the solution to the equation 4(2-3x) = x - 2(2x + 1) is x = 10/9.
whats the answer 4 (2 - 3x) = x - 2 (2x + 1)
1 answer